2009
DOI: 10.1111/j.1467-8624.2009.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Social Cognitive Neuroscience: Insights From Deafness

Abstract: The condition of deafness presents a developmental context that provides insight into the biological, cultural, and linguistic factors underlying the development of neural systems that impact social cognition. Studies of visual attention, behavioral regulation, language development, and face and human action perception are discussed. Visually based culture and language provides deaf children with affordances that promote resiliency and optimization in their development of visual engagement, executive functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 133 publications
(152 reference statements)
1
43
0
1
Order By: Relevance
“…This delay does not affect deaf children from deaf families who are exposed to a signed language from birth (Peterson & Siegal, 1999). Thus, the case of environmental influences in ToM development in deaf children is of great theoretical interest since they offer an opportunity to disentangle some of the variables thought to be of importance in this respect (Corina & Singleton, 2009). Previous studies have investigated the ways in which children's ToM development is fostered by interaction with caregivers, and have shown that deaf children's early experiences of communicative interaction with their hearing parents are very different compared to hearing children (Harris & Chasin, 2005;Meadow-Orlans & Spencer, 1996;Moeller & Schick, 2006;Morgan et al, 2014;Vaccari & Marschark, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…This delay does not affect deaf children from deaf families who are exposed to a signed language from birth (Peterson & Siegal, 1999). Thus, the case of environmental influences in ToM development in deaf children is of great theoretical interest since they offer an opportunity to disentangle some of the variables thought to be of importance in this respect (Corina & Singleton, 2009). Previous studies have investigated the ways in which children's ToM development is fostered by interaction with caregivers, and have shown that deaf children's early experiences of communicative interaction with their hearing parents are very different compared to hearing children (Harris & Chasin, 2005;Meadow-Orlans & Spencer, 1996;Moeller & Schick, 2006;Morgan et al, 2014;Vaccari & Marschark, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…To be classified as a native signer, participants had to have deaf parents and report their acquisition of ASL began prior to age three. The criterion of having deaf signing parents creates the sociocultural experience of full access to a visual language by adults who understand how to guide visual attention and scaffold visual language during the critical period of language acquisition (Corina & Singleton, 2009;Mayberry, 2007).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Although it has been considered that deaf individuals are superior in high-level visual information processing, such as peripheral vision and the perception of moving objects (Armstrong et al, 2002;Bavelier et al, 2006;Corina and Singleton, 2009), the present study showed that these individuals also translate visual information to auditory or phonological information. The visual memory index of the WMS-R in the present study did not show significant differences between the hearing and deaf groups.…”
Section: Discussionmentioning
confidence: 52%
“…It has also been shown that deaf individuals have better visual information processing abilities than hearing individuals, e.g., wider peripheral vision (Armstrong et al, 2002;Bavelier et al, 2006;Corina and Singleton, 2009). These previous studies predicted that deaf individuals process visual information prior to auditory or phonological information.…”
Section: Discussionmentioning
confidence: 97%